Early Control of PTH and FGF23 in Normophosphatemic CKD Patients: A New Target in CKD-MBD Therapy? - Oliveira, Rodrigo B. (American Society of Nephrology, 2010)
Background and objectives: Levels of parathyroid hormone (PTH) and the phosphaturic hormone FGF23, a fibroblast growth factor (FGF) family member, increase early in chronic kidney disease (CKD) before the occurrence of hyperphosphatemia. This short-term 6-wk dose titration study evaluated the effect of two phosphate binders on PTH and FGF23 levels in patients with CKD stages 3 to 4. Design, setting, participants, and measurements: Patients were randomized to receive over a 6-wk period either calcium acetate (n = 19) or sevelamer hydrochloride (n = 21). Results: At baseline, patients presented with elevated fractional excretion of phosphate, serum PTH, and FGF23. During treatment with both phosphate binders there was a progressive decline in serum PTH and urinary phosphate, but no change in serum calcium or serum phosphate. Significant changes were observed for FGF23 only in sevelamer-treated patients. Conclusions: This study confirms the positive effects of early prescription of phosphate binders on PTH control. Prospective and long-term studies are necessary to confirm the effects of sevelamer on serum FGF23 and the benefits of this decrease on outcomes.